2023
DOI: 10.2147/dmso.s389964
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Switching from Dipeptidyl Peptidase-4 Inhibitors to Glucagon-Like Peptide-1 Receptor Agonists on Bone Mineral Density in Diabetic Patients

Abstract: Purpose Diabetes increases the risk of fragility fractures. As a result, when choosing a diabetes treatment, whether the drug affects bone density should be taken into account. The goal of this study was to determine how switching from dipeptidyl peptidase-4 inhibitors (DPP-4i) to glucagon-like peptide-1 receptor agonists (GLP-1RA) influenced bone mineral density (BMD) in diabetic patients. Patients and Methods In this retrospective cohort study, diabetic patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
1
8
0
1
Order By: Relevance
“…There are conflicting data on this subject, and long-term studies with large groups are needed. [ 30 , 31 ] There was no significant change in BMI and BMD with treatment in the glargine group. Similar to our study, there are studies in the literature showing that BMD does not change with glargine treatment [ 9 ] and there are studies showing that it increases differently with our study.…”
Section: Discussionmentioning
confidence: 95%
“…There are conflicting data on this subject, and long-term studies with large groups are needed. [ 30 , 31 ] There was no significant change in BMI and BMD with treatment in the glargine group. Similar to our study, there are studies in the literature showing that BMD does not change with glargine treatment [ 9 ] and there are studies showing that it increases differently with our study.…”
Section: Discussionmentioning
confidence: 95%
“…Although an improvement of glycemic control and a larger weight loss was observed, the GLP‐1 RA group experienced a more significant decrease in the lumbar spine BMD than the group continuing DPP‐4i treatment (−0.028 g/cm 2 versus −0.019 g/cm 2 , p = 0.041, adjusted for body mass index [BMI]). ( 48 ) However, in the study examining bone turnover markers, a 6‐month exposure to exenatide in people with T1D did not result in any changes in BMD, as assessed through measurements of the whole body, hip, lumbar spine, and forearm. ( 42 ) Furthermore, in a trial involving obese people without diabetes who were on antipsychotic treatment, a 3‐month exposure to exenatide did not lead to any changes in BMD in the lumbar spine, femoral neck, or total hip.…”
Section: Effects Of Incretins On Bone Healthmentioning
confidence: 94%
“…However, an observational study evaluating the switch in treatment from DPP4-i to GLP-1 RA report an improved glycemic status but significantly decreased lumbar spine BMD in patients switching to GLP-1 RA compared to patients staying on DPP4-i treatment [38 ▪ ]. Although the groups had similar body mass index, HbA1c and BMD at baseline there may be some residual confounding in relation to which patients switched from DPP4-i to GLP-1 RA [38 ▪ ]. This is in contrast to previous studies where patients with type 2 diabetes treated with GLP-1 RA preserved hip and lumbar spine BMD compared to placebo in spite of a weight loss in the active treated group [39], and obese women treated with GLP-1 RA preserved bone mineral content, based on whole body scans, despite a 12% weight loss [40].…”
Section: Evidence Within the Recent Yearmentioning
confidence: 99%
“…A recent systematic review including data from meta-analyses, randomized controlled trials, and observational studies concluded that treatment with GLP-1 RA does not impact BMD [37]. However, an observational study evaluating the switch in treatment from DPP4-i to GLP-1 RA report an improved glycemic status but significantly decreased lumbar spine BMD in patients switching to GLP-1 RA compared to patients staying on DPP4-i treatment [38 ▪ ]. Although the groups had similar body mass index, HbA1c and BMD at baseline there may be some residual confounding in relation to which patients switched from DPP4-i to GLP-1 RA [38 ▪ ].…”
Section: Evidence Within the Recent Yearmentioning
confidence: 99%